THE ROLE OF GROWTH FACTORS IN THE FUNCTIONING OF THE PLACENTAL SYSTEM - Eshimbetova , G.Z.; Musakhodzhayeva , D.A.; Shaikhramova, N.N.; Jurayeva, D.M.; Kholmatova, S.V. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Objective: to study serum growth factors in women with placental dysfunction (PD). Material and methods. The study involved 47 pregnant women, with a gestation period of 26-40 weeks, with an established diagnosis of placental dysfunction, who were under observation in the obstetric department of the City Maternity Complex No. 3 in Tashkent. Determination of serum levels of growth factors was carried out by ELISA, in accordance with the manufacturer’s recommendations. Results. It was found that pregnant women with PD at 26-40 weeks of gestation have significant dysregulation of growth factors and vascular activity, which is manifested in a significant decrease in the levels of VEGF-A and PlGF in the peripheral blood serum, as well as a significant increase in the level of sFlt-1. These changes lead to a pronounced imbalance in the ratio of sFlt-1 to PlGF, which can contribute to deterioration of placental function and is associated with the development of pathological conditions.